1998
DOI: 10.1128/aem.64.9.3336-3345.1998
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Bacterial Populations in Human Feces Measured by Fluorescent In Situ Hybridization with Group-Specific 16S rRNA-Targeted Oligonucleotide Probes

Abstract: Six 16S rRNA-targeted oligonucleotide probes were designed, validated, and used to quantify predominant groups of anaerobic bacteria in human fecal samples. A set of two probes was specific for species of the Bacteroides fragilis group and the speciesBacteroides distasonis. Two others were designed to detect species of the Clostridium histolyticum and theClostridium lituseburense groups. Another probe was designed for the genera Streptococcus andLactococcus, and the final probe was designed for the species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
411
4
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 949 publications
(439 citation statements)
references
References 35 publications
20
411
4
4
Order By: Relevance
“…This suggests that these allelic probes were reporting on distinct subpopulations of the bacterial group, and thus neither is reporting on the entire group present at any one time. Regarding absolute coverage, as noted above, the two direct quantification methods report maximum values within one (slot blots) or one-half (qPCR) order of magnitude of the 10 11 bacteria per gram of feces reported by microscopy and fluorescence in situ hybridization (Langendijk et al, 1995;Franks et al, 1998;Suau et al, 1999;Harmsen et al, 2002). We consider this a rather good agreement, given the previously documented diversity of targets in fecal specimens.…”
Section: The Animals and Their Bacteriasupporting
confidence: 63%
“…This suggests that these allelic probes were reporting on distinct subpopulations of the bacterial group, and thus neither is reporting on the entire group present at any one time. Regarding absolute coverage, as noted above, the two direct quantification methods report maximum values within one (slot blots) or one-half (qPCR) order of magnitude of the 10 11 bacteria per gram of feces reported by microscopy and fluorescence in situ hybridization (Langendijk et al, 1995;Franks et al, 1998;Suau et al, 1999;Harmsen et al, 2002). We consider this a rather good agreement, given the previously documented diversity of targets in fecal specimens.…”
Section: The Animals and Their Bacteriasupporting
confidence: 63%
“…Molecular analyses have mainly been targeted at ribosomal RNA and, more speci¢cally, at 16S rRNA [7]. Applied to faecal microbiota, molecular approaches based on the direct study of 16S rRNA genes [5] or using 16S rRNA probe hybridisation [8,9] have revealed the predominance of four phylogenetic groups gathering the six dominant cultivable genera. The Bacteroides group comprises the genus Bacteroides and also encloses the genera Prevotella and Porphyromonas.…”
Section: Introductionmentioning
confidence: 99%
“…Although molecular methods were consistent in terms of dominant groups [12], a more thorough analysis of the data acquired independently revealed di¡erences in the proportions of each phylogenetic group, depending on the approach used. For instance, the Bacteroides group is by far the main group in terms of rRNA index when using dot-blot hybridisation [9,13], while the C. coccoides group is the main one in terms of the number of cells when using £uorescent in situ hybridisation (FISH) [8]. These inconsistencies between studies could be explained by di¡erent probe spec-i¢cities or sampling strategies.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to develop an effective monitoring tool to directly detect and quantify selected probiotic bacteria (Souza et al 2012;Pandiyan, Balaraman, Thirunavukkarasu, George, Subaramaniyan, Manikkam & Sadayappan 2013;Skjermo, Bakke, Dahle & Vadstein 2015). Fluorescent in situ hybridization (FISH) has been widely applied in medical research, but its application to environmental research has been slower for its labourand cost-intensive with low throughput (Langendijk, Schut, Jansen, Raangs, Kamphuis, Wilkinson & Welling 1995;Franks, Harmsen, Raangs, Jansen, Schut & Welling 1998;Harmsen, Raangs, He, Degener & Welling 2002). An indirect enzyme-linked immunosorbent assay (indirect ELISA) was developed to detect and quantify bacteria cells by specific antigen-antibody interactions (Charneux, Lorin, Vitry, Antonicelli, Reguiai, Barbe & Bernard 2011;Su, Li, Pan & Xue 2016).…”
Section: Discussionmentioning
confidence: 99%